Evolution of Oral Solid Dosage Forms (Tablets): A Comprehensive Review of Advanced Manufacturing Technologies and Delivery Systems - Rapolu. Ashok Kumar; Vankudothu Kalyan; Voggu Jatin; Palamoor Lingam; Palthya Navaneetha; Bheemanapally Bharghav; Suthakaran Raj (International Journal of Pharmacy and Analytical Research, 2026)
The pharmaceutical landscape is shifting from conventional single-unit tablets toward sophisticated, patient- centric delivery systems that balance therapeutic efficacy with manufacturing efficiency. This review provides a comprehensive overview of five pivotal advancements in oral drug delivery: Bi-layer tablets, Orally Disintegrating Tablets (ODTs), Multi-Unit Pellet Systems (MUPS), Hot Melt Extrusion (HME), and 3D Printing. Bi-layer and MUPS technologies are analyzed for their ability to manage incompatible active pharmaceutical ingredients (APIs) and provide programmed release profiles, such as combined immediate and sustained release. To address the challenge of patient compliance, particularly in pediatric and geriatric populations, the formulation of ODTs using super- disintegrants is explored. Furthermore, the review examines the transition from batch to continuous manufacturing through HME, a solvent-free process critical for enhancing the bio-availability of poorly soluble drugs. Finally, the trans-formative potential of 3D printing is discussed as the ultimate tool for personalized medicine and complex "poly-pill" architectures. By integrating these technologies, the pharmaceutical industry can achieve precise control over drug release kinetics, reduce side effects, and transition toward individualized therapy.Rapolu. Ashok Kumar1